Polymer-based platforms by electric field-assisted techniques for tissue engineering and cancer therapy. (January 2014) - Guarino, Vincenzo; Cirillo, Valentina; Altobelli, Rosaria; Ambrosio, Luigi
<x xml:space="preserve">Abstract</x> A large variety of processes and tools has been investigated to acquire better knowledge on the natural evolution of healthy or pathological tissues in 3D scaffolds to discover new solutions for tissue engineering and cancer therapy. Among them, electrodynamic techniques allow revisiting old scaffold manufacturing approach by utilizing electrostatic forces as the driving force to assemble fibers and/or particles from an electrically charged solution. By carefully selecting materials and processing conditions, they allow to fine control of characteristic shapes and sizes from micro to sub-micrometric scale and incorporate biopolymers/molecules (e.g., proteins, growth factors) for time- and space-controlled release for use in drug delivery and passive/active targeting. This review focuses on current advances to design micro or nanostructured polymer platforms by electrodynamic techniques, to be used as innovative scaffolds for tissue engineering or as 3D models for preclinical in vitro studies of in vivo tumor growth.